Combined Stress Conditions in Melon Induce Non-additive Effects in the Core miRNA Regulatory Network - Villalba-Bermell, Pascual; Marquez-Molins, Joan; Marques, María-Carmen; Hernandez-Azurdia, Andrea G.; Corell-Sierra, Julia; Picó, Belén; Monforte, Antonio J.; Elena, Santiago F.; Gomez, Gustavo G. (Frontiers in Plant Science, 2021)
Climate change has been associated with a higher incidence of combined adverse environmental conditions that can promote a significant decrease in crop productivity. However, knowledge on how a combination of stresses might affect plant development is still scarce. MicroRNAs (miRNAs) have been proposed as potential targets for improving crop-productivity. Here, we have combined deep-sequencing, computational characterization of responsive miRNAs and validation of their regulatory role in a comprehensive analysis of melon’s response to several combinations of four stresses (cold, salinity, short day, and infection with a fungus). Twenty-two miRNA families responding to double and/or triple stresses were identified. The regulatory role of the differentially expressed miRNAs was validated by quantitative measurements of the expression of the corresponding target genes. A high proportion (ca. 60%) of these families (mainly highly conserved miRNAs targeting transcription factors) showed a non-additive response to multiple stresses in comparison with that observed under each one of the stresses individually. Among those miRNAs showing non-additive response to stress-combinations, most interactions were negative suggesting the existence of functional convergence in the miRNA-mediated response to combined stresses. Taken together, our results provide compelling evidences that the response to combined stresses cannot be easily predicted from the study individual stresses.